Induction of classical transplantation tolerance in the adult. - Qin, S; Cobbold, S; Benjamin, R; Waldmann, H (1989)
Transplantation tolerance across histoincompatibilities in multiple non-H-2 minors (B10.BR into CBA/Ca) and "minor" plus H-2D (B10.A into CBA/Ca) antigens has been achieved successfully by combined adult bone marrow transplantation and treatment with CD4 and CD8 mAbs. The tolerant state was confirmed by permanent acceptance of donor strain skin grafts, and in vitro unresponsiveness to donor cells. Tolerance was associated with partial donor chimerism to various degrees. Tolerance to minor transplantation antigens induced in this manner was restricted to recipient-type MHC. The possibility was raised that tolerance resulted, at least in part, from clonal anergy rather than deletion.